Group Communication of Pesinauan as a Means of Preserving Osing Culture in Kemiren Village: Komunikasi Kelompok Pesinauan sebagai Preservasi Budaya Osing di Desa Kemiren - Maulana, Achmad Rifaldi; Sinduwiatmo, Kukuh (Kanal: Jurnal Ilmu Komunikasi, 2026)
The Osing culture in Kemiren Village, Banyuwangi, faces globalization challenges that shift the younger generation’s interest away from local traditions. Pesinauan serves as a community-based non-formal educational institution aimed at preserving cultural values, norms, and practices through dialogic and participatory group communication. This study employs the Group Achievement Theory, which emphasizes the roles of input, mediating variables, and output in group productivity. A qualitative approach with a case study method was chosen to explore the dynamics of group communication within Pesinauan. Data were collected through interviews, observation, and documentation, and analyzed using Miles and Huberman’s model. The results show that interactions in Pesinauan are active through cultural activities such as Mocoan Lontar Yusup, Gandrung Dance, and traditional crafts, using the Osing language as the medium of instruction. Communication patterns are egalitarian, involving elders, youth, and learners equally. Hands-on learning strengthens cultural identity, fosters creativity, and enhances collective awareness. Challenges such as intergenerational perception differences are managed through open deliberation. The discussion confirms that group communication in Pesinauan serves a dual function: as a medium for cultural knowledge transfer and as a means of character building based on local values. In conclusion, Pesinauan effectively functions as both a center for cultural preservation and an agent of Osing value regeneration, with its strengths lying in egalitarian communication, cross-generational engagement, and contextual learning that adapts to contemporary challenges.